SUSTAINABLE FISHERIES MANAGEMENT BASED ON SYARIAH BIOECONOMICS MODEL - Wahyudin, Yudi; Mahipal, Mahipal (Politeknik Kelautan dan Perikanan Dumai, 2024)
This article aims to provide a new perspective and paradigm in sustainable fisheries management by introducing and integrating sharia principles and approaches into the fisheries bioeconomic model. The initial model is carried out by introducing ZIS parameters into the Gordon-Schaefer fisheries bioeconomic model. The amount of ZIS can provide encouragement to build and develop a sustainable sharia fisheries bioeconomic management model. Factors that influence the success of fishing gear (q) to be able to catch fish, the ability of the environmental carrying capacity (K) to be able to maintain fish reproduction and growth, and the ability of the fish themselves to grow and develop in achieving a certain biomass (r) are something that is essentially desired as a gift from the Almighty on the basis of the efforts of His servants to fulfil the ZIS command. In addition, the income of His servants (fishermen) which is influenced by the price (p) of fish and the efficiency of the cost per unit of catch (c) that must be spent to obtain fish is an inseparable part of the existence of income which is also a gift from Allah. The five parameters of the sharia bioeconomic of fisheries (r, q, K, p, c) which are influenced by the presence of the ZIS factor are the fortune and way of Allah SWT to bestow blessings, gifts, and welfare to His servants (fishermen) who have fulfilled ZIS. This sustainable sharia bioeconomic management model of fisheries is based on the paradigm and perspective of the community (fishermen) in carrying out fishing through the fulfilment of ZIS maximally and sustainably which is carried out by always hoping for the pleasure and blessings of Allah SWT, it is hoped that it can change the lives, lives and livelihoods of the fishing community.